Sensitivity of APTIMA HPV E6/E7 mRNA test in comparison with hybrid capture 2 HPV DNA test for detection of high risk oncogenic human papillomavirus in 396 biopsy confirmed cervical cancers. Issue 7 (6th January 2016) - Basu, Partha; Banerjee, Dipanwita; Mittal, Srabani; Dutta, Sankhadeep; Ghosh, Ishita; Chowdhury, Nilarun; Abraham, Priya; Chandna, Puneet; Ratnam, Sam
Abstract : The sensitivity of E6/E7 mRNA‐based Aptima HPV test (AHPV; Hologic, Inc.) for detection of cervical cancer has been reported based on only a small number of cases. We determined the sensitivity of AHPV in comparison with the DNA‐based Hybrid Capture 2 HPV test (HC2; Qiagen) for the detection of oncogenic HPV in a large number of cervical cancers at the time of diagnosis using cervical samples obtained in ThinPrep (Hologic). Samples yielding discordant results were genotyped using Linear Array assay (LA; Roche). Of 396 cases tested, AHPV detected 377 (sensitivity, 95.2%; 95%CI: 93.1–97.3), and HC2 376 (sensitivity, 94.9%; 95%CI: 92.7–97.1) with an agreement of 97.2% (kappa 0.7; 95%CI: 0.54–0.87). Among six AHPV+/HC2‐ cases, LA identified oncogenic HPV types in four including a type 73 and was negative in two. Among five AHPV‐/HC2+ cases, LA detected oncogenic HPV types in two including a type 73 and was negative in three. Of 14 AHPV‐/HC2‐ cases, 13 were genotyped. LA detected oncogenic HPV types in six, non‐oncogenic types in three, and was negative in four. This is the largest study to demonstrate the sensitivity of AHPV for the detection of invasive cervical cancer and this assay showed equal sensitivity to HC2. J. Med. Virol. 88:1271–1278, 2016 . © 2015 Wiley Periodicals, Inc.